Queensland wave climate : wave monitoring program annual summary. - Queensland. Coastal Impacts Unit; Queensland. Department of Science, Information Technology and Innovation (Brisbane QLD : Department of Science, Information Technology and Innovation, 2015)
This summary of wave climate in Queensland is prepared annually by the Coastal Impacts Unit. Annual wave reports supplement the reporting ability of the Unit by providing information on wave climates in Queensland. The information presented here summarises the primary analyses of wave data recorded using Datawell Waverider buoys positioned off the Queensland coastline from 1 November to 31 October.
Later issues published by the Department of Environment and Science (2015/2016-)
Prepared by: Coastal Impacts Unit, Science Delivery Division, Department of Science, Information Technology and Innovation.
Title from PDF cover page (viewed on September 12, 2018).
Also available online (as at 12/09/18) at: https://publications.qld.gov.au/dataset/wave-data-recording-program.
Available online at the State Library of Queensland.
Also available online (as at 12/09/18) at: https://publications.qld.gov.au/dataset/wave-data-recording-program.
Keywords: Ocean waves -- Pacific ocean -- Measurement -- Periodicals; Ocean waves -- Queensland -- Measurement -- Periodicals